Stabilized leachates: Ozone-activated carbon treatment and kinetics - Javier Rivas, F. (2003)
Ozone has been used as a pre-oxidation step for the treatment of stabilized leachates. Given the refractory nature of this type of effluents, the conversion of some wastewater quality parameters has been moderate after 1 h of ozonation (i.e. 30% chemical oxygen demand (COD) depletion). Ozone uptake was calculated in the interval 1.3–1:5 g of ozone per gram of COD degraded. An optimum dose of ozone has been experienced in terms of biodegradability of the processed effluent (60 min of treatment, 1 103 mol L1 ozone inlet feeding concentration and 50 L h1 gas flowrate). pH and other typical hydroxyl radical generator systems exerted no influence on the efficiency of the process, suggesting the negligible role played by the indirect route of oxidation (generation of hydroxyl radicals). The ozonated effluent was thereafter treated in a second adsorption stage by using a commercial activated carbon. Removal levels up to 90% of COD in approximately 120 h were experienced for adsorbent dosages of 30 g L1 : Both steps, the single ozonation and the adsorption stage have been modelled by using different pseudoempirical models. r 2003 Elsevier Ltd. All rights reserved.